Surface Modification of Additively Manufactured Inconel 718 Alloy by Low-Energy High-Current Electron Beam Irradiation - KAYNAK, YUSUF (My University, 2024)
The effect of low-energy high-current electron beam (LEHCEB) irradiation on the microstructure and nanohardness of Inconel 718 alloy produced by laser powder bed fusion additive manufacturing is investigated. The LEHCEB irradiation is applied to the alloy at three energy levels, and the resulting microstructural analysis of irradiated surfaces is conducted. The findings from this study demonstrate that the LEHCEB irradiation substantially changes the as-built microstructure showing intragranular dendrites of different shapes and irregular-shaped Laves phases. The columnar structure is formed in the modified near-surface layer as a result of rapid heating and cooling during LEHCEB irradiation. Furthermore, all Laves phases dissolve in the modified layer. Nanoindentation hardness of the irradiated layer of the alloy increases from 593 ± 23 to 693 ± 13 Hv with the highest energy density of 15 J cm−2. This increment is attributed mainly to the dissolution of Laves phases and the formation of an ultrafine columnar structure where the columns are separated from each other by the district regions containing very thin interlayers of a secondary phase and a high amount of dislocations.
Keywords: Fizik; Yoğun Madde 1:Yapısal, Mekanik ve Termal Özellikler; Temel Bilimler; Mühendislik ve Teknoloji; Physics; Condensed Matter 1: Structural, Mechanical and Thermal Properties; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Malzeme Bilimi; FİZİK, YOĞUN MADDE; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); MATERIALS SCIENCE; PHYSICS; PHYSICS, CONDENSED MATTER; Genel Malzeme Bilimi; Fizik Bilimleri; Yoğun Madde Fiziği; General Materials Science; Physical Sciences; Condensed Matter Physics; additive manufacturing; Inconel-718; irradiation; low-energy high-current electron beam; microstructure; nanohardness; phase composition